2011
DOI: 10.4018/jisscm.2011100102
|View full text |Cite
|
Sign up to set email alerts
|

Development of Holistic Framework Incorporating Collaboration, Supply-Demand Synchronization, Traceability and Vertical Integration in Agri-Food Supply Chain

Abstract: Successful implementation of food supply chains in improving the productivity and operational efficiency by some companies made many other firms and researchers courteous about this fast developing field. For successful strategies, organizations in agri-food business are aiming to bring all its stakeholders in close cooperation. The agri-food supply chain aims at optimal warehousing and location design, supply-demand synchronization, checking price variations and ultimately minimizing waste and improving produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…Many authors develop and validate RFID-based traceability systems for perishable products and cold chain monitoring (Chen et al , 2014; Sharma and Patil, 2011; Todorovic et al , 2014). The use of the information collected by these systems to support decision-making and distribution strategies is also investigated (Shi et al , 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many authors develop and validate RFID-based traceability systems for perishable products and cold chain monitoring (Chen et al , 2014; Sharma and Patil, 2011; Todorovic et al , 2014). The use of the information collected by these systems to support decision-making and distribution strategies is also investigated (Shi et al , 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, it is suggested that the use of IT for integration with suppliers has a greater impact on operational performance than integration with customers. Sharing the same idea, Cheng [27] found that buyers benefit more from the exchange of information with suppliers than with customers, and that a possible explanation would be the existence of an incentive for suppliers to adopt the same type of technologies, due to the desire to want to keep the business. An example is what happened to the multinational Wal-Mart, which, in order to improve its operational performance, asked its main suppliers to adopt the same information systems and technologies, and they in turn made the same request to their suppliers.…”
Section: Analysis and Exploration Of Key Concepts And Cluster Structuresmentioning
confidence: 99%
“…To name a few, Hobbs et al [132] examine the vertical scope of partnerships between Integrators-Contracting Firms-Retailers-Consumers to enhance the client satisfaction (trust). Under the same scope, Sharma and Patil [127], Kalykova et al [74], and Imami et al [143] explore the collaboration among Farmer-Processor, Processor-Retailer, Wholesaler-Exporter, and Farmers/Primary Producer-Transporter-Logistics Provider-Processor-Distributor-Consumer. Hardman et al [149] examine the spectrum of relationship and point out that when improving the collaboration among Producers-Packers-Exporters, the production planning, delivery scheduling and quality control of the CSCs will be improved.…”
Section: By Types Of Collaborative Partnersmentioning
confidence: 99%